Identifikasi Bakteri Escherichia Coli Pada Sampel Daging Bakso Sebagai Pangan Jajanan Anak Sekolah (PJAS) - Ayuning Setiara; Jistisya Maria Agnes Br Tarigan; Melisa Anandari; Nabila Husna; Nita Hulzana; Selfiana Hanson Pangaribuan; Sesil Audia Br Sibarani (Algoritma : Jurnal Matematika, Ilmu pengetahuan Alam, Kebumian dan Angkasa, 2024)
Pangan Jajanan Anak Sekolah (PJAS) is one of the foods consumed by people in Indonesia, especially by children and adolescents. This food is very vulnerable to contamination by microorganisms that can damage and can be toxic to the human body when consumed. Microbes can contaminate food through water, dust, air, soil, processing equipment (during the production or preparation process) as well as secretions from the intestines of humans and animals. The method used is literature review by collecting, evaluating, and synthesizing existing studies in the scientific literature. In this case using a search engine such as google scholar. The years obtained from articles from 2018 to 2024 are relevant to the topic of this research. The topic used is the identification of Escherichia coli bacteria in meatball meat samples as school snack food (PJAS), this method is used to gain an in-depth understanding of Escherichia coli bacteria in meatball meat samples as school snacks. According to the World Health Organization (WHO), an estimated 600 million people globally (nearly 1 in 10 people) fall ill including diarrhea, kidney and liver failure, brain and nerve disorders, reactive arthritis and cancer from food-borne diseases, with 420,000 deaths reported in 2010. Food-borne illnesses arise from the consumption of contaminated food, which can be.